Prognostic significance of helicobacter pylori-infection in gastric diffuse large B-cell lymphoma - Yuan Cheng; Yinan Xiao; Ruofan Zhou; Yi Liao; Jing Zhou; Xuelei Ma (BMC Cancer, 2019)
Abstract Background Helicobacter pylori (H. pylori) is thought to have an oncogenic effect on the development of gastric malignancies. However, the effect of H. pylori status on the prognosis of gastric diffuse large B-cell lymphoma (DLBCL) remains unconfirmed. This study aimed to identify the prognostic importance of H. pylori infection in de novo gastric DLBCL. Methods One hundred and twenty-nine patients diagnosed with primary de novo gastric DLBCL at the West China Hospital of Sichuan University from 1st January 2009 to 31st May 2016 were included. The clinical features of the patients were documented. H. pylori status was assessed via urease breath tests and histologic examinations. The prognostic value of H. pylori was verified via univariate and multivariate analyses. Results Over a median follow-up of 52.2 months (range 4–116), the 5-year overall survival (OS) for all patients was 78.7%. Patients with H. pylori infections had significantly better 5-year PFS and OS than did the H. pylori-negative subgroup (5-year PFS, 89.3% vs. 74.1%, P = 0.040; 5-year OS, 89.7% vs. 71.8%, P = 0.033). Negative H. pylori status and poor ECOG performance were independent negative prognostic indicators for both PFS and OS (PFS, P = 0.045 and P = 0.001, respectively; OS, P = 0.021 and P < 0.001, respectively). Conclusions H. pylori status in de novo gastric DLBCL can be a promising predictor of disease outcome, and patients with negative H. pylori status require careful follow-up since they tend to have a worse outlook.